2017
DOI: 10.1016/j.omtm.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Human Tregs from Cryopreserved Umbilical Cord Blood for GMP-Compliant Autologous Adoptive Cell Transfer Therapy

Abstract: Umbilical cord blood is a traditional and convenient source of cells for hematopoietic stem cell transplantation. Thymic regulatory T cells (Tregs) are also present in cord blood, and there is growing interest in the use of autologous Tregs to provide a low-risk, fully human leukocyte antigen (HLA)-matched cell product for treating autoimmune diseases, such as type 1 diabetes. Here, we describe a good manufacturing practice (GMP)-compatible Treg expansion protocol using fluorescence-activated cell sorting, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 60 publications
5
59
0
Order By: Relevance
“…Our prior work has demonstrated that tTregs can be isolated from human CB and expanded with exceptional purity and lineage stability (32). Here, we extend our prior studies optimizing Treg expansion protocols to further characterize the transcriptional profile and repertoire characteristics of human Tregs from CB in comparison to those isolated from APB.…”
Section: Introductionmentioning
confidence: 70%
“…Our prior work has demonstrated that tTregs can be isolated from human CB and expanded with exceptional purity and lineage stability (32). Here, we extend our prior studies optimizing Treg expansion protocols to further characterize the transcriptional profile and repertoire characteristics of human Tregs from CB in comparison to those isolated from APB.…”
Section: Introductionmentioning
confidence: 70%
“…An ongoing concern in adoptive cell transfer therapies is the paucity of informative markers reflecting epigenomic stability of expanded cell populations, as for example, in the expansion of umbilical cord blood derived T-regulatory cells (Seay et al 2017). …”
Section: Cold Springmentioning
confidence: 99%
“…Therefore, it is important to develop more regulatory-specific and potent TDSs such as soluble or particulate tolerance vehicles (e.g., nanoparticles, microspheres, and liposomes) containing different tolerogenic agents such as rapamycin, aryl-hydrocarbon receptor ligands, retinoic acid, vitamin D3, and cytokines such as interleukin (IL)-10 and transforming growth factor (TGF)-β [31,34]. Other TDSs are of a cellular nature in which tol-DCs or Tregs produced ex vivo are reintroduced in vivo [35,36], or are genetically modified gastrointestinal bacterial strains expressing autoantigen and tolerogenic cytokines [37]. Note that apoptotic tolerance vehicles are in this cellular class of TDSs.…”
Section: Discussionmentioning
confidence: 99%